Factors Related to the Performance of Malaysian Rubber Mini-Estates - Diolo-Ontok, Medin (1991)
Despite the national government' s great concern to improve the socio-economic plight of the rubber smallholders, they still remain one of the poor sectors in this country. The RISDA rubber mini -estate scheme was implemented in 1979 for this concern. The major objective of this study was to identify factors related to performance of rubber mini-estate schemes. Specifically, it aimed to : determine relationships among the identified participants', officers' and contractors' characteristics with the dependent variables, i.e. the acreage replanted, first year of tapping in the scheme, income of participants during the programme and identify additional criteria for measuring performance of the miniestates.